Correlation of Total Antioxidant Capacity Measured by Ferric Reducing Ability of Plasma (FRAP) Assay with the Severity of Preeclampsia - Hermawan, Martin (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To analyze correlation between total antioxidant capacity measured by Ferric Reducing Ability of Plasma (FRAP) assay with severity of preeclampsia. Method: The cross sectional method was used in this study to compare TAC of four different groups of study, consists of normal pregnancy, mild preeclampsia, severe preeclampsia and eclampsia. The study consisted of 15 women in each group. All of the subjects met the inclusion criteria and were admitted to Dr. Hasan Sadikin Hospital and itâs district hospital. The study was conducted from August until September 2011. 3 ml blood samples were taken and were measured by FRAP assay in the laboratory PRODIA Jakarta. Result: There was no significant difference (p